Precise GNSS Positioning and Navigation: Methods, Challenges, and Applications - Zhang, Zhetao; Yu, Wenkun; Casula, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The research scope of this reprint mainly focuses on GNSS data processing methods; GNSS applications; precise GNSS positioning and navigation; theories, models, and methods for processing wojGNSS errors; multi-GNSS positioning technologies; positioning and navigation methods under challenging environments; and low-cost GNSS positioning and navigation.